2016
DOI: 10.1353/ajm.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Igusa’s local zeta function

Abstract: The origin and development of the Igusa local zeta function, by Igusa and others, is presented. In particular, we discuss the various conjectures Igusa made and the notable results that have so far been obtained. We also explain how topological and motivic zeta functions arose from the Igusa local zeta function and present the current status of the analogous conjectures. Igusa's conjecture on exponential sums that are related to his zeta function is described, and along with the progress made towards its resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…The basic tool he used is called the π-adic stationary phase formula, which was first introduced by Igusa [8] and then became a very powerful tool in the study of the rationality of Z f (s, χ) in arbitrary characteristic case. For more progress in the rationality of Igusa's local zeta function, see [11].…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…The basic tool he used is called the π-adic stationary phase formula, which was first introduced by Igusa [8] and then became a very powerful tool in the study of the rationality of Z f (s, χ) in arbitrary characteristic case. For more progress in the rationality of Igusa's local zeta function, see [11].…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…In [28], we showed that the p-adic open string N −point tree amplitudes are bonafide integrals that admit meromorphic continuations as rational functions, by relating them with multivariate local zeta functions (also called multivariate Igusa local zeta functions [29,30]). Moreover Denef and Loeser [31] established that the limit p approaches to one of a local zeta function gives rise a new object called topological zeta function, which is associated with a complex polynomial.…”
Section: Jhep08(2018)043mentioning
confidence: 99%
“…The functions Z (N ) (s; I, 0, K e ) and Z (N ) (s; T I, 1, K e ) are multivariate local zeta functions, see Apendix B. The local zeta functions are related with deep arithmetical and geometrical matters, and they have been studied extensively since the 50s, see [30,44] and references therein.…”
Section: Non-archimedean String Zeta Functionsmentioning
confidence: 99%
“…Determining the convergence of the amplitudes in momentum space is a difficult task, both in the standard and p-adic case; however, for the latter, this was precisely done for the N-point tree amplitudes in [8]. In this article we show (in a rigorous mathematical way) that the p-adic open string N-point tree amplitudes are bona fide integrals that admit meromorphic continuations as rational functions, this is done by associating to them multivariate local zeta functions (also called multivariate Igusa local zeta functions) [25][26][27][28]. In [6] we establish in a rigorous mathematical way that Koba-Nielsen amplitudes defined on any local field of characteristic zero (for instance R, C, Q p ) are bona fide integrals that admit meromorphic continuations in the kinematic parameters.…”
Section: Introductionmentioning
confidence: 99%